The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3109/13880209.2011.556650
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antibacterial activity and cytotoxicity of essential oils ofTanacetum partheniumin different developmental stages

Abstract: This study demonstrates the occurrence of camphor/bornyl acetate chemotype of T. parthenium in western regions of Iran. The finding showed also the studied oils have relatively good antibacterial activity without significant toxicity, thus have great potentiality to be used as natural health product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 24 publications
5
34
0
3
Order By: Relevance
“…The percentage yield of the oil herb was slightly different from the previously reported data. 15,21 Results showed that essential oil of the feverfew had 13 compounds which had formed 98.72 percent of the entire essential oil. Camphor (43.97%), chrysanthenyl acetate (12.46%) and farnesol (7.54%) were the main components of the essential oil among identified compounds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The percentage yield of the oil herb was slightly different from the previously reported data. 15,21 Results showed that essential oil of the feverfew had 13 compounds which had formed 98.72 percent of the entire essential oil. Camphor (43.97%), chrysanthenyl acetate (12.46%) and farnesol (7.54%) were the main components of the essential oil among identified compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Also, according to the reports on T. parthenium growing in Iran showed similarities in terms of composition of the major constituents of this herb and differences in terms of the percentage of these compositions. 14,15,21,24 In comparison with one of the analyses of the oil of roots from T. parthenium (collected from Karaj), camphor and chrysanthenyl acetate were identifid as 30.2% and 26.5%, respectively. Monoterpenoids were the main components of the oil (66.5%), but sesquiterpenoides (20%) had low percent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially Tanacetum parthenium (L.) Schultz Bip (feverfew) is a known remedy for the treatment of various diseases, including arthritis, fever, vertigo, migraine, menstrual disorders, stomach-ache, toothache, insect bites and psoriasis (Ernst and Pittler, 2000). According to recent studies, essential oils and extracts of Tanacetum genus exhibit anti-inflammatory (Brown et al, 1997;Ghantous et al, 2013;Mordujovich-Buschiazzo et al, 1996;Park et al, 2011;Sur et al, 2009), anticancer (Ghantous et al, 2013), antibacterial (Habibi et al, 2009;Hethelyi et al, 1991;Holopainen and Kauppinen, 1989;Mohsenzadeh et al, 2011), antiviral (Onozato et al, 2009), antifungal (Hethelyi et al, 1991), antihelmintic (Godinho et al, 2014), insecticidal (Hough-Golstein and Hahn, 1992;Nottingham et al, 1991;Panasiuk, 1984;Schearer, 1984;Suomi et al, 1986) and antiprotozoal effects (Izumi et al, 2008;Tiuman et al, 2005). Many studies have been reported on the essential oil composition of various Tanacetum species (El-Shazly et al, 2002;Goren et al, 2001;Greche et al, 2000;Judzentiene and Mockute, 2005;Kandemir et al, 2008;MajedJabari et al, 2002;Marongiu et al, 2009;Mockute and Judzentiene, 2004;Monfared et al, 2002;Piras et al, 2014;Polatoglu et al, 2011;Rohloff et al, 2004;Weyerstahl et al, 1999) and camphor, 1,8-cineole, ␣-thujone, carv...…”
Section: Introductionmentioning
confidence: 97%
“…(Asteraceae), commonly known as feverfew herb (Cretnik et al, 2005;Hamedi et al, 2013). Various biological activities, like antioxidant, anticancer, antimicrobial, and anti-inflammatory properties of T. parthenium, are attributed to the presence of parthenolide (Jain & Kulkarni, 1999;Kwok et al, 2001;Lesiak et al, 2010;Mohsenzadeh et al, 2011;Wu et al, 2006). Also, parthenolide has been reported for its anti-inflammatory, antileishmanial, antifungal, antioxidant, and anticancer properties (Hehner et al, 1999;Herrera et al, 2005;Mathema et al, 2012;Tiuman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%